Effect of the Proportion of Rice Flour; Modified White Corn Flour (Zea mays L) and Addition of Sodium Tripolyphosphate (STPP) to Vermicelli Characteristics - Ramadani, Elsa Firliana; Rosida, Rosida; Wicaksono, Luqman Agung (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Vermicelli, a form of food diversification from rice, was investigated in this study using modified rice flour and white corn flour (Zea mays L). The modification of white corn flour, employing the BIMO-CF starter containing various lactic acid bacteria, aimed to increase amylose levels. Sodium Tripolyphosphate (STPP) was added to improve the vermicelli's physical properties, including stickiness, color, hardness, and chewiness. A 2-factor Complete Randomized Design (CRD) with two replicates was utilized. Data were analyzed using ANOVA at a 5% significance level, followed by a DMRT 5% post-hoc test if significant effects were observed. Results demonstrated significant interactions between the proportions of rice flour, modified white corn flour, and STPP on vermicelli’s water content, ash content, protein content, starch content, amylose content, elasticity, and rehydration power. The optimal treatment was a combination of rice flour and modified white corn flour in a 50:50 ratio with 0.3% STPP, resulting in vermicelli with 8.65% water content, 0.72% ash content, 5.60% protein content, 52.5% elasticity, 127.5% rehydration power, and average sensory scores of 4.04 for color, 4.20 for aroma, 3.88 for taste, and 4.16 for texture, indicating favorable consumer acceptance.